The Influence of Compensation, Motivation, and Commitment to Teacher Performance At Junior High School Somba Opu Sungguminasa, Gowa District - muhtazib muhtazib (Institute for Research and Community Service, 2019)
Student achievement can be determined by the performance of professional teachers, so teachers must be able to improve their professional in responding to the challenges of the times so rapidly. The purpose of this study was to determine and analyze the effect of compensation, motivation, and commitment to teacher performance at Junior High School Somba Opu Sungguminasa, Gowa District, and to find out the dominant factors influencing. The study population was all teachers at at Junior High School Somba Opu Sungguminasa, Gowa District amounting to 32 people. Because the population is small or less than 100 people, the entire population is sampled (100% sample). The analytical method used is multiple linear regression analysis. The results showed that simultaneously and partially all independent variables consisting of compensation, motivation, and commitment had a positive and significant effect on the performance of Somba Opu Sungguminasa Junior High School teachers, Gowa District, where compensation was the most significant factor influencing.